Noninvasive Detection of Intracranial Hypertension by Novel Ultrasound Time-Harmonic Elastography - Kreft, Bernhard; Tzschätzsch, Heiko; Shahryari, Mehrgan; Haffner, Paula; Braun, Jürgen; Sack, Ingolf; Streitberger, Kaspar Josche (Investigative Radiology, 2022)
OBJECTIVE: A method for measuring intracranial pressure (ICP) noninvasively has long been sought after in neurology and neurosurgery. Treatment failure in individuals presenting with unspecific symptoms such as headache, gait disturbance, or visual impairment occurring in response to increased ICP can lead to irreversible brain injury, progressive disability, and death. Guidelines for diagnostic ICP measurement recommend intracranial placement of pressure tip catheters or lumbar puncture (LP) despite their invasiveness and possible complications. As ICP fluctuations are closely associated with changes in brain stiffness, ultrasound elastography could be a valid method to detect ICP noninvasively and with short examination times. MATERIALS AND METHODS: In this pilot study, we have investigated the use of time-harmonic shear waves, introduced into the brain by an external shaker, and measured in real-time by transtemporal ultrasound, for deducing a noninvasive imaging marker sensitive to elevated ICP. To this end, we developed cerebral ultrasound time-harmonic elastography for the noninvasive quantification of shear wave speed (SWS) as a surrogate marker of cerebral stiffness in a short examination time of a few minutes. RESULTS: We found that SWS in patients enrolled for LP with confirmed intracranial hypertension was 1.81 ± 0.10 m/s, distinguishing them from healthy volunteers with excellent diagnostic accuracy (1.55 ± 0.08 m/s; P < 0.001; area under the curve, 0.99). Interestingly, values in symptomatic patients decreased to normal stiffness immediately after LP (1.56 ± 0.06 m/s, P < 0.001). Moreover, invasively measured opening pressure correlated with SWS measured before LP and liquid volume drained through the spinal tap with the SWS difference between the 2 measurements. CONCLUSIONS: Collectively, our results suggest a tight link between cerebral stiffness and ICP and demonstrate that intracranial hypertension can be detected noninvasively within short examination times, opening avenues for diagnostic applications of cerebral ultrasound time-harmonic elastography in neurology and emergency medicine.
CRIS-Team Scopus Importer:2022-08-03